Endangered species - Lampton, Christopher (New York F. Watts, 1988)
Explains what species are, how they become extinct, and the effect of extinction on the ecology, and surveys endangered species of plants and animals and possible solutions.
Keywords: Endangered species -- Juvenile literature; Endangered plants -- Juvenile literature; Extinction (Biology) -- Juvenile literature; Wildlife conservation -- Juvenile literature